AeU aspires to be a research-based institution. - The, Star (The STAR, 2011)
Becoming a research based institution of higher learning in Malaysia.School of Graduate Studies, dean, Prof Dr Siow Heng Loke : research opportunities university does not bind to any terms or conditions.